Water quality of the main tributaries of the Paraná Basin: glyphosate and AMPA in surface water and bottom sediments - Ronco, Alicia Estela (2016)
The Parana River, the sixth largest in the world, is the receptor of pollution loads from tributaries traversing urban and industrialized areas plus agricultural expanses, particularly so in the river’s middle and lower reaches along the Argentine sector. In the present study, we analyzed and discussed the main water quality parameters, sediment compositions, and content of the herbicide glyphosate plus its metabolite aminomethylphosphonic acid (AMPA) in water and sediments. Samples were obtained from distal positions in the principal tributaries of the Parana and the main watercourse during surveys conducted in 2011 and 2012 to monitor the basin. Only 15 % of the water samples contained detectable concentrations of glyphosate at an average concentration of 0.60 μg/L, while no detectable levels of AMPA were observed. The herbicide and metabolite were primarily present in sediments of the middle and lower stretch’s tributaries, there occurring at a respective average of 37 and 17 % in samples. The mean detectable concentrations measured were 742 and 521 μg/kg at mean, maximum, and minimum glyphosate/AMPA ratios of 2.76, 7.80, and 0.06, respectively. The detection of both compounds was correlated with the presence of sulfides and copper in the sediment matrix.